Incidence and Risk Factors of Hernia Mesh-Related Infections: A Systematic Review and Meta-Analysis - Qanita Izza Kemala; Ghina Nabila Aisyah; Nusaibah Hanina Najah (Medicinus, 2026)
Background: Prosthetic mesh lowers hernia‑recurrence rates but can precipitate infection; reported incidence and risk factors remain inconsistent. The objective of this systematic review and meta-analysis is to estimate the pooled incidence of hernia mesh infections and to identify the key risk factors associated with their development.Methods: A PRISMA 2020 search of PubMed, EMBASE and Scopus identified randomised, cohort and case‑control studies that reported mesh‑related infection incidence or risk factors ≥ 3 months after adult hernia repair. Two reviewers independently screened records, appraised bias (ROBINS‑I) and graded certainty (GRADE). Random‑effects meta‑analyses generated pooled proportions and risk ratio (RR).Result: Seven studies encompassing 57,653 repairs qualified. Infection incidence ranged 1.3 – 10.2 %; the pooled proportion was 4.9 % (95 % CI 2.6 – 7.4, I² = 87 %). Diabetes (RR 1.49, 95 % CI 1.13 – 1.97) and smoking (RR 1.43, 95 % CI 1.34 – 1.52) were consistent patient‑level risks, whereas obesity (RR 1.48, 95 % CI 0.68 – 3.22) and female sex (RR 1.08, 95 % CI 1.04 – 1.11) exerted smaller effects. Operative time > 2 h, emergency repair, large/PTFE or composite intraperitoneal meshes, and repeat surgery each roughly doubled infection odds. Certainty was low‑to‑moderate overall but high for diabetes and smoking; no publication bias was detected.Conclusions: Roughly one in twenty mesh repairs is complicated by infection. Optimising glycaemic control, enforcing smoking cessation, shortening operations and selecting macroporous meshes may meaningfully lower risk.